Benzo[b]carbazolediones Synthesis and Inhibitory Effects on Nucleotide Pyrophosphatases/Phosphodiesterases. Issue 9 (8th March 2019) - Huy Do, Hoang; Ejaz, Syeda Abida; Molenda, Ricardo; Ohlendorf, Lars; Villinger, Alexander; Khan, Shafi Ullah; Lecka, Joanna; Sévigny, Jean; Iqbal, Jamshed; Ehlers, Peter; Langer, Peter
Abstract: Two new and efficient methods for the synthesis of benzo[ b ]carbazolediones have been developed. Various derivatives were synthesized by either a three‐component one‐pot reaction or a two‐component domino reaction in moderate to good yield. Moreover, inhibition studies of these compounds against nucleotide pyrophosphatases (NPPs) have been carried out. An interesting and promising inhibitory effect was observed by the influence of different substituents. Substitution with a methyl group located at the indole moiety was found sensitive towards h ‐NPP1 (4b; IC50 ±SEM = 0.57 ± 0.05 μM), while the unsubstituted derivative exhibited a higher sensitivity towards h ‐NPP3 (4a; IC50 ± SEM = 0.16 ± 0.06 μM). Both derivatives presented non‐selective inhibition of both isozymes. Among all the derivatives, two derivatives with anisyl groups showed the highest selectivity towards h ‐NPP3 and no interaction with h ‐NPP1. Finally, the free binding energies were calculated and molecular docking studies were performed in order to provide an insight into putative binding modes of these inhibitors. Abstract : Two new and efficient methods for the synthesis of benzo[ b ]carbazolediones have been developed. Various derivatives were synthesized by either a three‐component one‐pot reaction or a two‐component domino reaction in moderate to good yield. Moreover, inhibition studies of these compounds against nucleotide pyrophosphatases (NPPs) have been carried out. An interesting and promising inhibitory effect was observed by the influence of different substituents.